Technology’s Role in Modern Marketing - Samantaray , Alaka (International Journal of Psychosocial Rehabilitation, 2019)
The paper focuses on understanding new developments that have influenced modern marketing today. The paper also discusses the conception of technology that has changed the marketing perspective. Thinking about marketing and technology’s role in it, understand that the face of 21st century marketing techniques has changed with new marketing ideas. Advertising is now increasingly technologically based, and the advent of a new marketing element is also known as digital marketing. Digital marketing focuses primarily on marketing through digital media devices such as smart phones and computers. The use and deployment of technology to sell a commodity at the right time plays an important role. Any new entrant’s launch process, be it product or service, where direct marketing is of real significance. Digital marketing is based on technologies or platforms such as websites, email, apps and social networks. Non-internet channels such as TV, radio, SMS or Internet channels such as social media, e-mail ads, and banner ads can also be used for digital marketing.